Perilaku Menyimpang Di Kalangan Pelajar: Pencegahan Dan Penanganan - Rianda, Muhammad Zaki; Anugerah, Saptiari Putra (Journal of Sustainable Education, 2024)
This research aims to explore and analyze deviant behavior among students and its impact on their academic and social development. Deviant behavior, which includes actions such as skipping school, drug abuse, fighting, and other criminal behavior, is an increasingly worrying phenomenon in the educational environment. This research used a survey method involving 300 students from various secondary schools in Kampar. Data were analyzed using descriptive and inferential statistical techniques. The research results show that deviant behavior among students has a significant negative correlation with their academic performance and social relationships. Students who are frequently involved in deviant behavior tend to experience decreased academic grades and difficulty in establishing positive social relationships. These findings highlight the important role of teachers, parents and schools in creating an environment that supports and prevents deviant behavior among students. Implementation of effective intervention programs and strong social support is necessary to address these issues and promote positive student development.